Sampled-Data Stabilization for Stochastic Systems Subject to Input Saturation and Its Application to Synchronization of Two Chua's Circuits - Huang, Yongjia; Deng, Feiqi; Wan, Fangzhe; Yu, Peilin; Sun, Yuanyuan (IEEE transactions on circuits and systems. II, Express briefs, 2023)
In this brief, we focus on the stabilization problem of a class of stochastic nonlinear systems under periodic sampled-data state feedback subject to input saturation. An auxiliary variable is introduced to handle the saturation nonlinearity as well as to characterize the estimate of the region of attraction of the origin (RAO). After discretizing the continuous-time systems and obtaining the iterative relations of sampling instants, sufficient stabilization criteria are established in the form of parametric conditions. Both mean square exponential stability and almost sure stability are considered. Based on our results, the relations among the estimate of RAO and controller gain, sampling period can be analysed clearly, which is demonstrated in the example. An application for synchronization of two Chua's Circuits is presented to illustrate the effectiveness of our results.